From flower to fruit: fruit growth and development in olive (Olea europaea L.)—a review - Rosati, Adolfo; Lodolini, Enrico Maria; Famiani, Franco (Frontiers in Plant Science, 2023)
The olive (Olea europaea L.) is the most cultivated tree crop in the Mediterranean and among the most cultivated tree crops worldwide. Olive yield is obtained by the product of fruit number and fruit size; therefore, understanding fruit development, in terms of both number and size, is commercially and scientifically relevant. This article reviews the literature on fruit development, from the flower to the mature fruit, considering factors that affect both fruit size and number. The review focuses on olive but includes literature on other species when relevant. The review brings the different factors affecting different phases of fruit development, addressed separately in the literature, under a single frame of interpretation. It is concluded that the different mechanisms regulating the different phases of fruit development, from pistil abortion to fruit set and fruit size, can be considered as different aspects of the same overall strategy, that is, adjusting fruit load to the available resources while striving to achieve the genetically determined fruit size target and the male and female fitness targets.